The Role of Youth in Overcoming Problems Related Sinabung Volcano Eruption - Yesi Chairani Tanjung; Erika Revida Saragih; Agus Purwoko (Randwick International of Social Science Journal, 2020)
Youth is one of the important human resources to increase their capacity. The number developed sufficiently. It shows that the nation's change is occurred very significant. In the disaster management, the youth certainly has a very important role to maintain the regional resilience. So that young people must be prepared to overcome threats and challenges related disasters that cannot be predicted. This study aims to determine how the role of youth in overcoming problems related Sinabung Volcano Eruption in Tiganderket Sub-District, Karo District, North Sumatra. This research uses qualitative methods. In this study, there are three informants interviewed. They are; 1) The Secretary of BPBD (Regional Disaster Management Agency, Karo District, 2) Youth Leaders, and 3) The local community who were presented in the form of scientific analysis. The results of this study indicate that: The Effectiveness of Youth's Role in overcoming Sinabung Volcano Eruption, Tiganderket Sub-district, Karo District, North Sumatra has not been able to tackle effectively. It can be measured from the level of Youth involvement to play a role in overcoming the disaster. It can look from the three phases which are Pre -disasters, During-disasters, and Post-disasters. The youth in Tiganderket Sub-district Only involved when the disaster happened.